Improving Learning Outcomes in Mathematics Classes via Rewards and Punishments: an Action Research - Situmorang, Hannah (Papanda Publisher, 2022)
Mathematics is one of the compulsory subjects given to students. However, several studies show that elementary school students still have difficulty in learning mathematics, causing very low learning outcomes. One effort that can be done is to use a variety of other learning methods that can increase students' interest in learning mathematics. This study aims to improve the learning outcomes of mathematics in elementary school students by applying the Rewards and Punishments method. This study uses a quantitative approach with the correlational method. The sample in this study was the third-grade students of HKBP No.1 Sibolga Private Elementary School, which amounted to 32 students who were determined by using a random sampling technique. Data collection techniques in this study are questionnaires and documentation studies. The results of this study indicate that the results of the correlation test prove that there is a relationship between reward and punishment on student learning outcomes. This shows that there is an effect of reward and punishment on student learning outcomes in grade III SD HKBP No.1 Sibolga. The conclusion of this research is that the Rewards and Punishments method is proven to be effective in improving student learning outcomes in mathematics subjects.